ERRATUM ON THE ARTICLE ‘The impact of the financial crisis on insider trading profitability in Belgium ’ (DOI: 10.3846/16111699.2011.652980) - Geyt, Debby Van; Cauwenberge, Philippe Van; Bauwhede, Heidi Vander (Journal of Business Economics and Management, 2013)
"Erratum on the article ‘The impact of the financial crisis on insider trading profitability in Belgium’ (doi: 10.3846/16111699.2011.652980)." Journal of Business Econimics and Management, 14(2), p. 432First published online: 04 Mar 2013